Influence of a pre-deformation on the critical strain for the onset of dynamic recrystallization of Ti-Nb microalloyed steels - Mostert, R.J. (Roelf) (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.